Kreativitas, Inovasi dan Transformasi Digital: Pengabdian Masyarakat kepada Pelaku UMKM - Nengyanti Nengyanti; Aulia Utami Putri; Annada Nasyaya; Farisha Sestri Musdalifah; Anang Dwi Santoso (Ilin Institute, 2023)
This community service intends to educate MSME actors in Pelabuhan Dalam Village, Ogan Ilir Regency about how to combat the COVID-19 epidemic through the use of creativity, innovation, and digital transformation. The program was separated into three stages: identification and analysis of problems, coaching and evaluation. The problem identification and analysis process involved interviews with community various stakeholders and village government officials, and revealed five major issues: a lack of public understanding of entrepreneurship development, a lack of innovation and technological use, difficulties with promotion (marketing), limited human resources and low quality, and low management quality. Coaching is conducted by the provision of three materials: creativity, innovation, and digital transformation, which comprise an understanding of the situation, as well as solutions and development strategies. Then, after comparing the data before and after coaching, it was established that there is now a gain in understanding about creativity, innovation, and digital transformation necessary for MSMEs to survive the COVID-19 pandemic before and after the program.